Estudo do comportamento crítico do Modelo Blume-Capel Spin-1 nas redes aleatórias de Voronoi-Delaunay - Fernandes, Francivaldo Pinheiro (2015)
In this work we study the critical properties of the spin-1 Blume-Capel model in two dimensions on Voronoi- Delaunay random lattices with quenched connectivity disorder. The system is treated by applying Monte Carlo simulations using the heat-bath update algorithm together with single histograms re-weighting tech- niques. We calculate the critical temperature as well as the critical exponents as a function of the crystal field -. It is found that this disordered system exhibits phase transitions of first- and second-order types that de- pend on the value of the crystal field. For values of - ≤ 3, where the nearest-neighbor exchange interaction J has been set to unity, the disordered system presents a second-order phase transition. The results suggest that the corresponding exponents ratio belong to the same universality class as the regular two-dimensional ferromagnetic model. There exists a tricritical point close to -t = 3:05(4) with different critical exponents. For -t ≤ - < 3:4 this model undergoes a first-order phase transition. Finally, for - ≥ 3:4 the system is always in the paramagnetic phase.